2007
DOI: 10.1088/1126-6708/2007/03/030
|View full text |Cite
|
Sign up to set email alerts
|

The one-loop renormalization of the gauge sector in the θ-expanded noncommutative standard model

Abstract: In this paper we construct a version of the standard model gauge sector on noncommutative space-time which is one-loop renormalizable to first order in the expansion in the noncommutativity parameter θ. The one-loop renormalizability is obtained by the Seiberg-Witten redefinition of the noncommutative gauge potential for the model containing the usual six representations of matter fields of the first generation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 43 publications
1
111
0
1
Order By: Relevance
“…In this work we consider the standard-model (SM) forbidden Z → γγ decay originating from the renormalizable gauge sector of the noncommutative standard model (NCSM) given in [1], which could be probed in highenergy collider experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we consider the standard-model (SM) forbidden Z → γγ decay originating from the renormalizable gauge sector of the noncommutative standard model (NCSM) given in [1], which could be probed in highenergy collider experiments.…”
mentioning
confidence: 99%
“…Even more, its noncommutative part is finite or free of divergences, so the noncommutativity parameter θ need not be renormalized. A detailed description of the renormalization procedure, including the results for the bare fields and couplings, is given in [1]. Finally, from the action (6) we extract the triplegauge boson terms which are not present in the commutative SM Lagrangian.…”
mentioning
confidence: 99%
“…Now taking into account the results of the θ 1 models [44,45], where in the NC SU(N) model [45] was explicitly shown that θ 1 parameter runs while having a negative β function, we conjecture that β functions associated with the parameters κ, η 1 , and (2η 4 − η 5 ) could be negative too. The (η 2 − η 3 ) difference should have a zero β function.…”
Section: Discussionmentioning
confidence: 87%
“…A very incomplete list of articles addressing problems in this research area includes refs. [78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99].…”
Section: Results For Nc Gauge Theoriesmentioning
confidence: 99%